ChemInform Abstract: Copper‐Catalyzed Synthesis of α, β‐Unsaturated Acylamides via Direct Amidation from Cinnamic Acids and N‐Substituted Formamides. Issue 51 (17th December 2013) - Yan, Hong; Yang, Hailong; Lu, Linhua; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract An efficient synthesis of α, β‐unsaturated acylamides via copper‐catalyzed direct amidation between readily available cinnamic acids and N‐substituted formamides is reported for the first time.